Effect of LIMA Harvesting Technique on Postoperative Drainage in Off-Pump CABG - Özülkü,Mehmet (2016)
Abstract Objective: We investigated the effects of pedicled and semiskeletonized left internal mammary artery (LIMA) harvesting techniques on postoperative drainage in patients subjected to off-pump CABG, ignoring other advantages or disadvantages of those techniques. Methods: The present study comprises a total of 160 subjects that underwent coronary artery bypass surgery in our clinic. Data were collected consecutively and retrospectively. An attempt was made to have similar groups in terms of demographic characteristics. Patients that underwent off-pump coronary artery bypass surgery by two surgical teams which differed only in LIMA harvesting technique were dichotomized and compared according to these techniques. The first group (Group 1) consisted of patients in whom LIMA was harvested with surrounding tissues using the pedicled technique. The second group (Group 2) consisted of patients in whom LIMA was harvested using the semiskeletonized technique, with the veins separated from surrounding connective tissues. Results: The mean amount of drainage in the first 24 hours was 706.1±234.2 ml vs. 591±258.8 ml (Group 1 vs. Group 2; P=0.005), the mean amount of drainage in the second 24 hours was 270±133.6 ml vs. 189.4±140.4 ml (Group 1 vs. Group 2; P<0.001), and the mean amount of total drainage was determined to be 976.1±306.9 ml vs. 781.2±335.5 ml (Group 1 vs. Group 2; P<0.001). Conclusion: It was observed that semiskeletonized LIMA presents reduced amount of postoperative drainage in the first and second 24-hour periods and total amount of drainage than pedicled LIMA, independent of pleural integrity.